Investment Climate Reform: Going the Last Mile The Bulldozer Initiative in Bosnia and Herzegovina - Herzberg, Benjamin (World Bank, Washington, D.C., 2013)
The author examines the Bulldozer Initiative in Bosnia and Herzegovina, an innovative reform methodology that successfully overcame the lack of political will and capacity at the government level through a bottom-up approach. Using an innovative grassroots and public awareness methodology, the initiative mobilized the local business community to bulldoze barriers by identifying concrete legislative changes and advocating for their adoption and implementation. By delivering fast results-50 reforms in 150 days-the initiative won the confidence of entrepreneurs and empowered them to institutionalize permanent grassroots reform committees. The force of this lobby group created political will by putting public pressure on the politicians to do their part to enact the reforms. Most important, it carried investment climate reform the last mile by delivering concrete, quantifiable results in all sectors of the economy. Over time, the initiative is establishing a dynamic of reform and public-private partnership that will facilitate the tackling of more complicated structural reforms. Complementing the systemic approach and framework reform efforts of governments and international agencies, competitiveness partnerships mobilize the local business community to catalog concrete problems across the full spectrum of investment climate concerns, pinpoint solutions, campaign for their adoption, and follow up on reform implementation. The author attempts to determine the applicability of competitiveness partnerships to different settings by modeling the interactions between several key success factors, thus providing a pertinent tool for development professionals, government officials, and private sector advocates who wish to establish a renewed implementation dynamic through this kind of results-oriented reform process.